THE URGENCY OF STANDARDIZING THE OPEN APPLICATION PROGRAMMING INTERFACE IN IMPLEMENTATION OF OPEN BANKING FOR CUSTOMER PROTECTION - Sakti, Muthia; Utami, Kery; Sulastri (Fakultas Hukum, Universitas Samudra, 2024)
Open banking with Open Application Programming Interface (open API) technology is an initiative aimed at streamlining the payment system in Indonesia. The open API allows banks to integrate their systems with digital financial service providers (fintech) and bold trade (e-commerce) providers by disclosing customer transaction data. This study investigates the urgency of open API standardization in implementing open banking in Indonesia. This study uses a normative juridical approach to secondary data. The data includes primary, secondary, and tertiary legal materials. In addition, it also uses qualitative normative data analysis methods. It was concluded that before the National Open API Payment Standard (SNAP) stipulation, the process of sharing data between banks and fintech and/or e-commerce still needed to be standardized but was only based on an agreement between the parties. Banking in Indonesia has various open API standards that can affect the protection of customer data. According to the Financial Services Authority Regulation Number 12/POJK.03/2018, the relationship between banks, fintech, and/or e-commerce in providing digital banking services based on agreements between parties needs to be stronger. OJK is indeed present as a supervisory agency. However, the parties will eventually come back to a deal between themselves. Unlike the Regulations of the Financial Services Authority, the Regulations of the Members of the Board of Governors, which form the legal basis for SNAP, provide standards that must be complied with by both service providers and service users. However, implementing SNAP-based open APIs still requires personal data protection regulations.